SOCIALISAT ION OF MODERN INDIVIDUAL IN THE SOCIAL PEDAGOGY OF JUOZAS VAI TKEVIČIUS - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2009)
The article makes an attempt to actualise the contribution of J. Vaitkevičius to establishment of fundamentals of social pedagogy, which are concurrent with development of individual’s spiritual culture. Employing comparative analysis, the attitudes of J. Vaitkevičius and other authors to the essence and meaning of socialisation in the human ontogenesis are described. The links between socialisation and world outlook are presented as a distinguishing feature of J. Vaitkevičius socialisation concept: world outlook, which consists of worldview and emotional attitude, reveals the level of individual’s socialisation and the quality of separate types of world outlook directly depends on this level. The article also presents J. Vaitkevičius’ integral system of socialisation factors where family is prioritised and seen as an initial institution of socialisation linking an individual with other institutions such as school and society. The thought presented by J. Vaitkevičius that in the times of general disorientation in values it is urgent to stimulate the three institutions to revive eternal common human and national values and to combine them with modern innovations. The role of an educator, as a subject of socialisation, a representative of intelligentsia, a torch of light, the good, the wise, the beautiful and the true as well as an example for school learners. It is emphasised that school learners’ parents, state and society have to consider educators and to create favourable conditions for their physical, mental and spiritual development.